Evidence for ethnicity and location as regulators of the newborn blood metabolome: a monozygous twin study - Jiang, Huimin; Han, Ting-Li; Yang, Jing; Yang, Yang; Wang, Fengdi; Chen, Yuelu; Huang, Nana; Mansell, Toby; Craig, Jeffrey M.; Scurrah, Katrina J.; Novakovic, Boris; Baker, Philip N.; et al. (Frontiers in Nutrition, 2024)
Introduction: Monochorionic, diamniotic (MCDA) monozygotic twins share nearly all genetic variation and a common placenta in utero. Despite this, MCDA twins are often discordant for a range of common phenotypes, including early growth and birth weight. As such, MCDA twins represent a unique model to explore variation in early growth attributable primarily to in utero environmental factors.Methods: MCDA twins with a range of within-pair birth weight discordance were sampled from the Peri/postnatal Epigenetic Twin Study (PETS, Melbourne; n=26 pairs), Beijing twin study (BTS, Beijing n=25), and the Chongqing Longitudinal Twin Study (LoTiS, Chongqing; n=22). All PETS participants were of European-Australian ancestry, while all Chinese participants had Han ancestry. The average of the birth weight difference between the larger and smaller co-twins for all twin pairs was determined and metabolomic profiles of amino acids, TCA cycle intermediates, fatty acids, organic acids, and their derivatives generated from cord blood plasma by gas chromatograph mass spectrometry. Within and between co-twin pair analyses were performed to identify metabolites specifically associated with discordance in birth weight. Multivariable regression and pathway enrichment analyses between different regions were performed to evaluate the geographical effects on the metabolism of MCDA twin pairs. Results: PETS twins showed a markedly different metabolic profile at birth compared to the two Chinese samples. Within-pair analysis revealed an association of glutathione, creatinine, and levulinic acid with birth weight discordance. Caffeine, phenylalanine, and several saturated fatty acid levels were uniquely elevated in PETS twins and were associated with maternal BMI and average within pair birth weight, in addition to birth weight discordance. LoTiS twins had higher levels of glutathione, tyrosine, and gamma-linolenic acid relative to PETS and BTS twins, potentially associated with eating habits.This study highlights the potential role of underlying genetic variation (shared by MZ twins), in utero (non-shared by MZ twins) and location-specific (shared by MZ twins) environmental factors, in regulating the cord blood metabolome of uncomplicated MCDA twins. Future research is needed to unravel these complex relationships that may play a key role in phenotypic metabolic alterations of twins independent of genetic diversity.